THE VALIDITY OF FNAA AND AAS METHOD FOR ANALYSIS OF Cu AND Fe ELEMENTS IN BIOTA SAMPLES - Sunardi Sunardi; Samin Samin; C. Supriyanto (Indonesian Journal of Chemistry, 2009)
The validity test of Fast Neutron Activation Analysis (FNAA) and Atomic Absorption Spectrometry (AAS) method for analysis of Cu and Fe elements in biota samples has been done. The validity test was represented by the validation test, homogenous test, Z-score test, t test and F test for both methods. The respective validity test results for Cu and Fe elements show that the FNAA precision test were 2.28% and 2.96% while the accuracy were 98.07% and 98.55%, and the precision of AAS validation test results were 1.72% and 2.29% and the accuracy were 98.50% and 98.35%. The uncertainty results for Cu and Fe by FNAA were 2.74% and 3.42%, while AAS were 2.98% and 3.73%. The limit of detection  for both methods of Cu and Fe were 1.05 µg/g and 1.35 µg/g, while AAS were 0.05 µg/g  and 0.904 µg/g, and the value of Z-score in the range ≥-2 and ≤+2 for both methods. In this case the precision, accuracy, uncertainty, limit of detection and value Z-score on both methods  are valid or property to be applied for element analysis. After FNAA and AAS methods were validated then were applied for determining of element contents in biota samples. From the homogenous test result was found that the samples of biota is homogeny, while t test shows that there is no significant difference in average concentration, F test of both methods shows that there is no difference in accuracy.